Numerical study on the effect of turbulence intensity on the separation behavior of magnetic particles under different magnet arrangements. Issue 5 (24th March 2023) - Li, Pinyi; Ye, Yong; Luo, Wei
ABSTRACT: The crucial problem of magnetic separation is improving the ability to capture magnetic particles in complex fluid flow. This paper develops a numerical model of an open gradient magnetic separation (OGMS) system to study the capture process of magnetic particles in laminar flow and turbulent flow under four kinds of magnet arrangement modes. The particle capture efficiencies of four inlet turbulence intensities are analyzed and compared with that of laminar flow. The results show that the particle capture efficiency of turbulent flow is higher than that of laminar flow under the same inlet velocity distribution in a small Stokes number. Moreover, the particle capture efficiency of high turbulence intensity is significantly higher than that of low turbulence intensity. The results also indicate that the axial alternating arrangement (AAA) can provide a stronger magnetic field, which is beneficial to particle capture.